COMPUTERIZED FEASIBILITY STUDY INFORMATION SYSTEMS IN DEBTOR CREDIT BANK INDONESIA - Totok Setianto; Djoko Triyono MSc (Jurnal Sistem Informasi, 1990)
With the development of economic activities or the development of a businessactivity of a company, then you should feel the need for growing businesses such.Therefore, the relationship between the growth of an economic activity or growthwith a business activity of the company with the existence of credit has a correlationcoefficient very close, both in its nature to be negative or positive.